Hubungan antara Asupan Zink dengan Kejadian Stunting pada Remaja di Sukoharjo Jawa Tengah - Sulistianingtias, Eva Laila, Dr. M. Shoim Dasuki, M.Kes (2017)
Adolescent growth need nutritional for maximun growth. Lack of nutrition in adolescencethere is a linear growth ardation cause stunting. In 2013 in Indonesian, the prevalence of adolescents aged 13-15 years who are stunting was 35.1%. Zinc is one of the important micronutrient.Zinc deficiency occurring at school age can result in physical growth or stunting disorder .in 2014 in Central Java as much as 94.2% of the study had a zinc intake <70% of Recommended Dietary Allowances.This study aimed to know relation between zinc intake with stunting in adolescents in Sukoharjo, Jawa Tengah. The research is an observational Analitic with cross sectional approach and purposive sampling. 71 samples who are passed the inclusion criteria. Rate zinc intake by interview Food Frequency Questionnaire Semi-kuantitatif.. Used chi-square statistic and SPSS 18.00 was use for analized the data.Based on chi square test zinc intake and stunting be obtaines p=0,001. The conclusionof this research is there is a correlation between zink intake and stunting in adolescents in Sukoharjo, Jawa Tengah